Phylogenetic relationships of the family Sphaeromatidae Latreille, 1825 (Crustacea: Peracarida: Isopoda) within Sphaeromatidea based on 18S-rDNA molecular data - Wetzer, Regina; Pérez-Losada, Marcos; Bruce, Niel L. (Zootaxa, 2013)
Based on 18S-rDNA sequences of 97 isopods including 18 Sphaeromatidea, we show Sphaeromatidae, Valvifera, Serolidae, and Ancinidae is a well supported clade. The within clade relationships of these taxa are not as definitively demonstrated because taxon sampling for some groups is still limited. In our analyses the Sphaeromatidae are shown to be unequivocally monophyletic. This is contrary to the morphology-based analysis by A. Brandt and G. Poore in 2003, which included only five Sphaeromatidae and found the family to be paraphyletic. The Ancinidae are also upheld, and the Valvifera is the sister taxon to Serolidae. Surprisingly Plakarthrium (Plakarthiidae) is nested within the Sphaeromatidae in most analyses. We point out short-comings in our sampling and suggest areas which would benefit from better sampling. We also review the long and convoluted nomenclatural history of the Sphaeromatidea, Sphaeromatoidea, and Sphaeromatidae.